Analysis of Secondary School Students’ Digital Game Addiction and Sportsmanship Behavior Levels According to Various Variables - HAZAR, Kürşat; HAZAR, Zekihan (Asian Journal of Education and Training, 2019)
The purpose of this research is to investigate the relationship between digital game addiction and fair play-sportsmanship behavior exhibited in physical education and sports lesson and to reveal the relationship between these two concepts. The research was designed according to quantitative research model and correlational scanning method was used. Sample: In this research, “typical case” method, one of the purposeful sampling methods, was used. In this context, 500 students (240 females, 260 males) who played digital games every day at least 30 min. and agreed to participate voluntarily in the research were interviewed using face-to-face interviews. Data Collection Personal Information Form, Sportspersonship Behavior Scale in Physical Education Course (SBSPEC), Digital Game Addiction Scale for Children (DGASC) there was used. The data were evaluated in SPSS 24 Package program and subjected to Independent Groups t-Test, ANOVA and Pearson Correlation analyzes. According to the results of the analysis, it was found that there were significant differences in the variables of gender, age, athlete’s license and game type. However, there was a positive correlation between the scale scores. Although there is no similar research on the subject when the literature is examined, the findings of the research on the variables discussed in the scope of the research will contribute significantly to the literature in terms of revealing the differences and relationships between the variables.